Enhancing prognostic accuracy in sepsis: a modified SOFA score incorporating lymphocyte count as an immune function marker - Huang, Zhishan; Cui, Ying; Zhang, Chen; Yu, Huijie; Chen, Lina; Wang, Xingxing; Zhou, Jiancang; Lan, Peng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSepsis, characterized by organ dysfunction due to a dysregulated immune response, is diagnosed using the Sequential Organ Failure Assessment (SOFA) score, which currently lacks immune function markers. The objective of this research is to enhance the predictive precision of SOFA for sepsis by integrating lymphocyte count as an indicator of immune system functionality.MethodsThis retrospective study was based on the MIMIC-IV database. The absolute lymphocyte count (ALC) was assessed as a predictive biomarker through multivariate analysis utilizing the Cox proportional-hazards model and was integrated into a modified SOFA score (ALC-SOFA). Associations between ALC-SOFA score and mortality were assessed using Kaplan-Meier survival analysis. Predictive performance was evaluated by comparing the area under the receiver operating characteristic (AUROC) curve for ALC-SOFA and the original SOFA score. The primary endpoint was the mortality rate at 28 days, with additional secondary endpoints including the mortality rates at 7 and 90 days.Results10,709 patients with sepsis were included in this study. ALC was significantly lower in nonsurvivors than in survivors (0.90 ± 0.62×109/L vs. 1.12 ± 0.69×109/L, P<0.001). Patients with lower absolute lymphocyte counts (ALC) exhibited a significantly higher risk of 28-day mortality (HR = 0.62, P<0.001). Survival analysis revealed higher mortality rates with increasing ALC-SOFA scores. The ALC-SOFA score demonstrated improved prognostic performance for 28-day mortality (AUROC = 0.680 vs. 0.664, P<0.001) and 90-day mortality (AUROC = 0.666 vs. 0.647, P<0.001) compared to the original SOFA score.ConclusionIncorporating ALC into the SOFA score significantly improves its ability to predict sepsis-related outcomes. The ALC-SOFA score provides a novel tool for prognostic assessment, highlighting the critical role of immune function in sepsis management.